THE ROLE OF DEVELOPMENT OF TRANSPORT TURISM IN ECONOMIC GROWTH - Alasgarova, Flora (Annals of Spiru Haret University. Economic Series, 2017)
Tourism is one of the necessary and very important sectors of country economy. Tourism has its appropriate inimitable characteristics that difference this sector from the other sectors. As to be in the other service industrial fields, in tourism sector the tourists come to the tourism destination place where the tourism services are supplied. To my observation and international experiences, it is hard to think of tourism industry without transportation. Transportation is mean where to carry the tourists to the relevant place where tourism services are accomplished. The article contains detailed information about the introduction to the concepts of tourism, theoretical approach to the tourism as service industry, the role of transport in tourism development, international experiences in transport tourism, development of transport tourismin Azerbaijan economy. The article can be considered as a useful resource for experts and researchers conducting research in this field.